OUTSTANDINGLY CITED AND MOST SIGNIFICANT PUBLICATIONS OF R. CHIDAMBARAM, A NUCLEAR PHYSICIST - Basavaraj Shivappa, Kademani; Kademani, B.S.; Kalyane, V.L. (Malaysian Journal of Library and Information Science, 2017)
Analyses 164 papers by R. Chidambaram, a nuclear physicist from India, published during 1958-93, and identifies highly cited papers as per Science Citation Index. His self evaluated ’most significant publications’ were also considered and it is found that the self assessment by a scientist about the significance of his papers may not always tally with the world’s opinion. The citation data were subjected to domain-wise and category-wise classification,and used to study time lag for receiving first citation to each paper, synchronous and diachronous self-citations, core journals in which his publications were published, publication density, publication concentration, journals in which his publications were cited, and influence of channels of communications and authorships on citedness.